Convergence of Antecedents on Work Motivation and Work Outcomes - Tuan, Luu Trong (Richtmann Publishing, 2011)
Numerous factors present in the contemporary organizational environment influence both content and process of motivation.From reviewing theories of work motivation, this paper seeks to construct an integrative motivation antecedents model that integrates theemergence of motivating behavior in work environment, identifies the right antecedents of the desired motivation, and then guidesmanagement on loading them into sources from where motivation will emerge. This paper, furthermore, illustrates the dynamic linkages inthis model through a case research.